2016
DOI: 10.1002/14651858.cd011319.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Drug-eluting balloon angioplasty versus uncoated balloon angioplasty for peripheral arterial disease of the lower limbs

Abstract: Based on a meta-analysis of 11 trials with 1838 participants, there is evidence of an advantage for DEBs compared with uncoated balloon angioplasty in several anatomic endpoints such as primary vessel patency (high-quality evidence), binary restenosis rate (moderate-quality evidence), and target lesion revascularization (low-quality evidence) for up to 12 months. Conversely, there is no evidence of an advantage for DEBs in clinical endpoints such as amputation, death, or change in ABI, or change in Rutherford … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 37 publications
1
50
0
2
Order By: Relevance
“…Therefore the cellular mechanisms responsible for atherosclerosis and neointimal hyperplasia are inhibited and its complications are prevented or postponed. DEB angioplasty demonstrated superior outcomes compared to PTA in infrainguinal lesions in many studies especially in DM patients . We also preferred DEB angioplasty for treatment in both BTK and BTA lesions in this study.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore the cellular mechanisms responsible for atherosclerosis and neointimal hyperplasia are inhibited and its complications are prevented or postponed. DEB angioplasty demonstrated superior outcomes compared to PTA in infrainguinal lesions in many studies especially in DM patients . We also preferred DEB angioplasty for treatment in both BTK and BTA lesions in this study.…”
Section: Discussionmentioning
confidence: 81%
“…Another important issue is that after a follow-up of 12 months, RBC was decreased significantly more in BTA group compared to BTK Primary, secondary patency, and mortality analysis with Kaplan Meier Curves many studies especially in DM patients. [9][10][11][12] We also preferred DEB angioplasty for treatment in both BTK and BTA lesions in this study.…”
Section: Definitionsmentioning
confidence: 99%
“…Commercially available drug-eluting stents may give hope in future; however, its common use is limited because of current cost-effective perspective. [23,24] Due to the complexity and diversity of the patients in our series, it was impossible to make up a control group for a randomized study. That was the limitation of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, balloon angioplasty provided poor patency outcomes in these vessels with restenosis rates as high as 70% at 1 year [12]. The advent of DCB was seen as a better alternative to balloon angioplasty, however, early clinical results have been limited, and to date, long-term benefit of DCB as compared to balloon angioplasty for treatment of atherosclerotic disease below-the-knee remains unknown [8][9][10]. Although our clinical study was not designed to compare with previous studies due to our small cohort, our reported TLR was greater coating embolization as shown in pre-clinical animal studies [15].…”
Section: Discussionmentioning
confidence: 99%
“…The BIOLUX P-II trial also showed similar patency loss between DCB and balloon angioplasty at 12 months in CLI patients [9]. Overall, DCB have not demonstrated clinical or angiographic advantage at 1 year follow-up as compared to balloon angioplasty [10].…”
Section: Introductionmentioning
confidence: 99%